Geo-Chicago 2016 : sustainable geoenvironmental systems : selected papers from sessions of Geo-Chicago 2016, August 14-18, 2016, Chicago, Illinois - Yesiller, Nazli; Zekkos, Dimitrios; Farid, Arvin; De, Anirban; Reddy, Krishna R. (American Society of Civil Engineers, 2016)
Contains 99 peer-reviewed papers on landfill engineering and geosynthetics used for geoenvironmental systems. Topics include: design, testing, and evaluation of geosynthetics in geoenvironmental systems; landfill engineering; sustainable barrier materials and systems; vertical barriers for geoenvironmental applications; slopes, dikes, and embankments; ground improvement; and geoengineering of mine wastes and industrial byproducts.
Sponsored by Geo-Institute of the American Society of Civil Engineers.
Keywords: Environmental geotechnology -- Congresses.; Sanitary landfills -- Linings -- Materials -- Congresses.; Geomembranes -- Congresses.; Engineered barrier systems (Waste disposal) -- Congresses.; Soil permeability -- Congresses.; Slopes (Soil mechanics) -- Stability -- Congresses.; Soils -- Testing -- Congresses.; elektronické knihy; electronic books